Interpretation of the Iqra’ Verse as the Foundation of Literacy in the Development of Islamic Education Management - Sriwiguna, Riris; Nuraeni, Eva; Anwar, Cecep; Rizkarima (Journal of Educational Management Research, 2025)
This study explores the integration of the Iqra’ verse (QS. Al-‘Alaq: 1–5) into Islamic educational management, aiming to develop a comprehensive literacy model that enhances leadership in Islamic educational institutions. The research addresses the gap between traditional Islamic values and modern educational management practices, particularly in Indonesia, where secular management models often dominate. By examining the epistemological, operational, and axiological dimensions of the Iqra’ verse, the study proposes a three dimensional literacy cycle for decision-making in educational institutions, emphasizing the importance of trust (amanah), justice, transparency, and consultation (shura). A qualitative, library-based research design with a thematic-tafsir approach was employed to analyze Qur’anic exegesis and contemporary educational management theories. The findings highlight that while existing literature addresses the role of Qur’anic principles in education, it lacks a systematic framework for operationalizing these values in management practices. The study contributes to the field by offering a novel model that bridges Qur’anic exegesis with modern management theory, urging further empirical testing and application in educational leadership.